2018
DOI: 10.1186/s12935-018-0673-1
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-218-5p inhibits cell growth and metastasis in cervical cancer via LYN/NF-κB signaling pathway

Abstract: BackgroundWe are committed to investigate miR-218-5 effects on the progression of cervical cancer (CC) cell and find out the molecular mechanism.MethodsGSE9750 was obtained from GEO database and R Limma package was applied to filter out dysregulated genes. The pathways were enriched by GSEA software, ClusterProfiler and enrichplot packages to predict the function of DEGs. The binding sites of LYN were detected by miRanda and TargetScan. The miR2Disease database was used to find miRNAs related with CC. The expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 38 publications
(42 reference statements)
0
30
0
Order By: Relevance
“…Even though E1, E2, L1 and L2 are always encountered in all HPVs, the other genes may vary (Stubenrauch et al, 2007;Nobre et al, 2009). The major oncogenes are considered to be E5, E6 and E7, which are also known for altering a variety of signaling pathways, such as Wnt, Notch, PI3K/Akt, MAPK, IFN and NF-κB and others (Gupta et al, 2018;Xu et al, 2018;Wang and Chen, 2019). However, studies have demonstrated that the HPV infection could alter the interaction between miRNAs and some of these pathways.…”
Section: Microrna Signaling In Hpv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though E1, E2, L1 and L2 are always encountered in all HPVs, the other genes may vary (Stubenrauch et al, 2007;Nobre et al, 2009). The major oncogenes are considered to be E5, E6 and E7, which are also known for altering a variety of signaling pathways, such as Wnt, Notch, PI3K/Akt, MAPK, IFN and NF-κB and others (Gupta et al, 2018;Xu et al, 2018;Wang and Chen, 2019). However, studies have demonstrated that the HPV infection could alter the interaction between miRNAs and some of these pathways.…”
Section: Microrna Signaling In Hpv Infectionmentioning
confidence: 99%
“…In the case of oral cancers caused by HPV16, the excessive expression of E6 and E7 oncogenes and the interaction with the NF-κB pathway lead to a better tumor differentiation, as well as an improved prognosis (Gupta et al, 2018). There were two miRNAs found to interact with this signaling pathway during HPV infection, and more specifically, in cervical cancers: miR-143-3p and miR-218-5p (Xu et al, 2018). Both of them have the mRNA LYN as a target, which was found to be highly expressed in HPV induced cervical cancers, thus increasing the activity of NF-κB pathway.…”
Section: Microrna Modulation Of Nf-κb Signaling In Hpv Infectionmentioning
confidence: 99%
“…Recently, miRNAs have been shown to be deregulated in pancreatic cancer, affecting several steps of initiation and aggressiveness of the disease by directly regulating target genes expression [25]. Among these miRNAs, miR-218-5p was found to play pivotal roles in many malignant tumors [26][27][28]. For example, miR-218-5p upregulation repressed gastric cancer growth and metastasis by directly regulating CDK6/CyclinD1 [28].…”
Section: Introductionmentioning
confidence: 99%
“…22 Subsequent research provided evidence that abundant miR-218 increased the radiosensitivity in cervical cancer cells. 23 More recently, Zhu et al 12,13 reported that miR-218 also produced anti-tumor effects on cervical cancer cells in vitro. In line with this, our results showed that miR-218 mimics significantly inhibited cervical cancer cell proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-218 was downregulated in cervical cancer, and miR-218 overexpression was found to inhibit cervical cancer cell viability, cell growth and metastasis, and promote apoptosis. 12,13 Bioinformatics using miRanda predicted that HULC and miR-218 have partially complementary sequences, suggesting that HULC may function as a "miRNA sponge" of miR-218. The prediction of target genes using TargetScan showed that there were binding sites between miR-218 and 3ʹ-UTR of the oncogenic tumor protein D52 (TPD52) mRNA.…”
Section: Introductionmentioning
confidence: 99%